One-pot fungal biomass-to-biodiesel process: Influence of the molar ratio and the concentration of acid heterogenous catalyst on reaction yield and costs - Bento, Heitor B.S. [UNESP]; Reis, Cristiano E.R.; Cunha, Pietro G.; Carvalho, Ana K.F.; De Castro, Heizir F. (Elsevier, 2021)
This work evaluates a microbial-based biodiesel production process through simultaneous esterification and transesterification of the lipid-rich fungal biomass using ethanol as both extractor and acyl acceptor. Two of the most influential parameters were evaluated, the molar ratio of ethanol to the oil, and the concentration of a heterogeneous acid catalyst (H3PMo/Al2O3), with responses in terms of conversion to ethyl esters and an estimated cost of the process variables. Fungal biomass of Mucor circinelloides was cultivated in sugarcane molasses media and the obtained oleaginous cells were used as the source of acylglycerols and free fatty acids for the trans/esterification reactions in a pressurized stainless-steel reactor at 200 °C for 6 h. Our results demonstrate that the effects of the two factors analyzed were significant, with an indication that increases in the molar ratio and catalyst favor the reaction yield. In the reaction system, a molar ratio of 120:1 (ethanol: oil) and 15 wt% of catalyst yielded 96.6% of ester content, which meets the minimum limit established by the international standards. Production costs were estimated in function of ethanol and catalyst price and indicated the selected parameters reflected the adequate configuration to reach the stablished minimum ester content.
Keywords: Biodiesel; Direct transesterification; Filamentous fungi; Heterogeneous catalysis; Single cell oil